Teaching reform and practice of object-oriented programming course. - Chen, Yanhua (SHS Web of Conferences, 2023)
This article aims at the deficiencies in the teaching of object-oriented programming courses in our school, guided by the OBE teaching concept, and aimed at cultivating applied talents. On the one hand, carry out teaching reform and practice, and carry out the design of the ideological and political education system of the course,so as to fully mobilize the initiative and enthusiasm of students,stimulate students' innovative ability, effectively cultivate students' innovative thinking ability and unity and cooperation ability, and then improve students' ability to solve problems.To provide guarantee for improving the quality of personnel training.